VA solid organ transplant programs: Maximizing the resources for current and future veterans. Issue 5 (26th March 2019) - Bennett, William M.
Abstract : The author presents a perspective and critique of the Veterans Affairs' solid organ transplant program. Gunnar's accompanying article is onpage 1288 .